“The working poor” phenomenon: notion, regional characteristics - Khussainova, Zh.S.; Yeskendir, N.N.; Kοrchevskaya L.A.; Gordeyeva, Y.A. (BUKETOV BUSINESS REVIEW, 2023)
Object: to focus on the concept, regional features of the phenomenon of “the working poor” in the Republic of Kazakhstan, to determine the share of working poor based on the latest statistical materials. Methods: statistical analysis, comparative analysis and table construction. Findings: The research results are based on the main results and conclusions: 1. despite the high importance of the issue of economic poverty and attempts to evaluate it empirically, there are different approaches to the definition of “working poor”. 2. a method of assessing labor income based on the base of mandatory pension contributions of it will allow to cover about 56.2% of employed in the local economy. Taking into account this approach to the analysis, in the Republic of Kazakhstan, “working poor” can be defined as employees who work in the official sector of the economy and transfer tax payments to the budget from income from labor activity within 2 ETS. At the same time, their estimated share in the Kazakhstani labor market is about 40%. Conclusions: the studies have shown that in the regions of the Republic it is necessary to introduce correction factors, addressing various reasons for differentiating labor incomes based on the specifics of the labor market and the living standard of the population.